Effect of rearing of calves (cow vs artificial) on the dam’s milk production : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Agricultural Science, Massey University, Palmerston North, New Zealand - Dhanushe, Himal (Massey University, 2025)
New Zealand has a unique dairy production system characterised by pasture-based feeding and highly seasonal calving, with most calves born in spring and artificially reared. However, rearing calves on cows is an alternative to improve the growth rate of calves. Little research has compared artificial and dam-suckling rearing, and its influence on milk yield and composition in lactating dairy cows remains unclear. Therefore, this study aimed to assess the effect of cow-rearing of calves on dams' milk production over an entire lactation period in a seasonal pasture-based, once-a-day milking herd in New Zealand. Thirty-nine cows (Jersey, Holstein-Friesian, and their crossbreeds) were assigned to either natural suckling (Cow, n = 20) or artificial rearing (Shed, n = 19) groups at calving. Cows in the Shed group had their calves removed within 36 hours of birth and had no contact with dams thereafter. Dams in the Cow group remained with their calves at all times except during milking, until weaning at a mean of 68 ± 15 days, reduced over three days. All cows were managed as a group on pasture and were milked once-a-day for their entire lactation. Daily meter milk data were collected until December, and monthly herd-test records were obtained throughout the season. During the pre-weaning phase, the Cow group recorded 489 kg lower milk yield, 33 kg less fat, 23 kg less protein, and 56 kg less milk solids than the Shed group (p < 0.0001). These differences correspond to the expected milk intake of calves (6–8 litres/day) directly from their dams under unrestricted suckling. Milk fat concentration differed between pre- and post weaning phases, and a significant Treatment x Phase interaction indicated a greater increase in fat concentration following weaning in cows rearing calves, while no within-phase treatment differences were observed. Cumulative milk yield, component yields, and concentrations were not significantly different between treatments post-weaning. Total lactation yields of milk, fat, protein, and milk solids were also not statistically different between groups. The Cow group exhibited a slightly later peak and greater lactation-curve persistency, although this did not translate into differences in overall season production. Extended cow–calf contact reduced saleable milk yield only during the pre-weaning period, reflecting milk diverted to calf growth rather than an actual drop in production and did not compromise overall lactation performance in this OAD, pasture-based system. Further research should quantify the actual milk suckled by calves, the long-term effects on udder health, reproductive performance, and whole-season milk solids output across successive lactations and assess calf growth and other on-farm implications to evaluate the potential benefits and trade-offs of rearing strategies within commercial pasture-based dairy systems.
Figure 3 is reused with permission.
Keywords: calf rearing; pasture-based; milk composition; lactation period; dam rearing; cow-calf contrast; 300302 Animal management